Garçons manqués and femmes fortes: Two ambivalent figures of butch lesbianism in women's football in Cameroon - Ndjio, Basile (African Studies Review, 2022)
With the enactment of anti-homosexuality laws in the 1960s, Cameroon's government officially endorsed heterosexualist ideologies which legitimize the alienation and criminalization of minority and nonconforming sexual and gender identities. One group, the so-called garçons manqués, embodies the stigmatized masculine or "butch" lesbian identity. The political management of lesbianism in Cameroon is ambivalent, however, with respect to sport, and particularly regarding the national pastime, football. Whereas masculine lesbians are routinely branded as "butches" or "sexual predators" who threaten African hetero-patriarchy, "strong women"" (femmes fortes) are celebrated as pivotal to the national ambition. Cameroon's government strategically amalgamates both heteronationalism and homonationalism in the interest of national pride.
Keywords: afrique; anthropologie; approches et analyses; butch; cameroun; discipline; discours dominant; hétérosexisme; personnes lesbiennes; ressource en ligne; régions géographiques; sciences humaines; sexisme; sport; systèmes d'oppressions

Gender and extreme metal: Understanding gender relations in the Montreal extreme metal scene with schipper's gender framework - Beauchamp, Caroline (Université Concordia, 2021)
Extreme metal is a masculine space, yet more and more women join in. They face a contradiction: as women, they are expected to adopt feminine behaviours; however, they are part of a subculture that valorizes warrior masculinity. I sought to understand the gender expectations of the Montreal extreme metal scene and interpret the contradictions encountered by women in this scene with the help of Schippers’ (2007) theoretical framework on gender. To do so, I conducted 16 individual interviews with women and men who take part in the scene. This research fills a gap in the literature on gender that derives from Connell and Schippers’ writings and addresses issues that the field of metal studies has brushed over. I found that metal men are the “default” participants in the scene. They are expected to be fine music connoisseurs and even become musicians. In contrast, women’s presence is heterosexualized and attributed to a romantic or sexual interest in metal men. Women are suspected of being “poseuses” or groupies with no real interest in the music until proven otherwise. To become legitimate participants, they have to overcome those expectations and prove that they are worthy of being viewed through the prism of masculinity rather than femininity. They do so by proving their exceptionality through manhood acts and distancing themselves from other women. Despite their gender transgressions, women’s presence does not fundamentally question gender relations but reaffirms the overall primacy of masculinity over femininity.
https://spectrum.library.concordia.ca/id/eprint/988125/
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; anthropologie; approches et analyses; discipline; genre; hétérosexisme; masculinité; montréal; mémoires/thèses; privilèges; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; stéréotypes de genre; systèmes d'oppressions; étude qualitative

‘Passionate aesthetics’: T-P gender practices and discourses, and the hierarchies within lesbian (lala) communities in contemporary mainland China - Wang, Yiran (Journal of Gender Studies, 2021)
En tant que couple masculin-féminin comparable aux genres lesbiens butch-femme dans les sociétés euro-américaines, les rôles de genre TP constituent des éléments vivants dans la sous-culture lesbienne, ou lala , de la Chine continentale contemporaine. Sur la base d'une étude ethnographique menée au milieu des années 2010 à Shanghai et dans la province du Yunnan, en Chine, et en appliquant le cadre théorique de « l'esthétique passionnée », j'étudie dans cet article les discours et les pratiques pertinents pour les genres TP . J’analyse comment les hiérarchies ont été (re)produites au sein des communautés lala et comment, dans ces processus, les compréhensions (hétéro)normatives du genre et de la sexualité sont devenues à la fois sources de connaissances et objets de critique. Je soutiens que des esthétiques passionnées multiples et concurrentes, y compris la forme dominante d'hétéronormativité en Chine et les connaissances mondialisées, voire occidentales, sur le genre et la sexualité, ont entraîné trois grands types de hiérarchie parmi les lalas : des hiérarchies entre les catégories TP , qui sont paradoxalement définies par la notion de « pureté » ; les hiérarchies dans les discours féministes et activistes LGBTQ, qui banalisent, voire font taire, les incarnations quotidiennes du TP ; et les hiérarchies entre masculinité et féminité, qui encouragent diverses pratiques de masculinité féminine tout en valorisant la masculinité plutôt que la féminité.
Keywords: 2000 à aujourd'hui; 2010-2019; anthropologie; approches et analyses; asie; chine; discipline; genre; hétérosexisme; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions